PARTICIPATORY COMMUNICATION FOR WASTE MANAGEMENT AT ANDARMAN COASTAL TOURIST ATTRACTIONS OF THE LOCAL ADMINISTRATIVE ORGANIZATIONS - Engchuan, Chaiporn; Panyawuttrakul, Haruthai; Sridee, Supaporn (Journal of Social Science and Cultural, 2023)
This research is for 1) Study participatory communication management. 2) Study the participatory communication process. and 3) study participatory communication in waste management of Andaman Sea coast tourist attractions of local government organizations. It is a qualitative research using in-depth interviews with Important informants include the president of the subdistrict administrative organization and the subdistrict municipality. Personnel of the Subdistrict Administrative Organization and Subdistrict Municipality Tour operator representative and community leaders There were a total of 24 village headmen/villages. The results of the research found that 1) Participatory communication management in waste management All three local administrative organizations emphasize public relations campaigns through participatory project activities such as workshops. Training seminar Demonstration lecture and integrate network partners Adhere to working principles and change perspectives, ideas, and understanding of waste management guidelines. From the role and duties of government agencies to the private sector, communities, citizens and working together as a network. 2) Participatory communication process in waste management Ao Nang Subdistrict Administrative Organization emphasizes "participatory communication", giving people the opportunity to participate in every step. Khok Kloi Subdistrict Administrative Organization emphasizes the participation process under the guidelines for creating a network according to the 1P3C model of Kamphaeng Subdistrict Municipality. Emphasis on the participation process of citizens, community leaders, organizational groups, and network partners in both the public and private sectors. 3) Guidelines for developing participatory communication in waste management. All 3 local government organizations create value from designing leftover materials. Strengthen knowledge new innovations and use communication processes creativity and the expertise of community leaders and citizens, together with the use of knowledgeable lecturers